2020
DOI: 10.1111/sms.13767
|View full text |Cite
|
Sign up to set email alerts
|

Pain and disability in women with patellofemoral pain relate to kinesiophobia, but not to patellofemoral joint loading variables

Abstract: Patellofemoral pain (PFP) affects one in four people of the general population and is characterized by peripatellar pain exacerbated by activities that load the patellofemoral joint (PFJ). 1,2 Research and the treatment of people with PFP have historically focused on mechanical factors that increase or alter patellofemoral joint loading, 3 with elevated PFJ loading

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Nine studies reported PFJRF during stair ambulation 28 38 39 41 42 48 65 84 85. During stair ascent, pooled peak PFJRF in healthy individuals was 3.2±0.7 BW28 38 39 41 48 84 based on six studies and 2.5±0.5 BW in those with patellofemoral pain based on three studies,38 42 65 and peak PFJRF in individuals with patellofemoral OA was 1.6±0.4 BW48 based on a single study (figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies reported PFJRF during stair ambulation 28 38 39 41 42 48 65 84 85. During stair ascent, pooled peak PFJRF in healthy individuals was 3.2±0.7 BW28 38 39 41 48 84 based on six studies and 2.5±0.5 BW in those with patellofemoral pain based on three studies,38 42 65 and peak PFJRF in individuals with patellofemoral OA was 1.6±0.4 BW48 based on a single study (figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported PFJRF during stair ambulation 28 38 39 41 42 48 65 84 85. During stair ascent, pooled peak PFJRF in healthy individuals was 3.2±0.7 BW28 38 39 41 48 84 based on six studies and 2.5±0.5 BW in those with patellofemoral pain based on three studies,38 42 65 and peak PFJRF in individuals with patellofemoral OA was 1.6±0.4 BW48 based on a single study (figure 3). During stair descent, pooled peak PFJRF in healthy individuals was 2.8±0.5 BW38 39 48 84 based on four studies and 2.6±0.8 BW in those with patellofemoral pain38 65 based on two studies, and peak PFJRF was 1.0±0.5 BW in individuals with patellofemoral OA48 based on one study (figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other non-mechanical factors such altered pain processing, kinesiophobia and catastrophism may also affect neural control and should be addressed in future studies. 4,38,39…”
Section: Clinical Interpretation Of Altered Neural Control Of Gait In...mentioning
confidence: 99%
“… 38 In addition, several studies focusing on kinesiophobia have shown this to be associated more strongly with function in PFP compared with physical factors such as patellofemoral joint loading variables, muscle strength, and flexibility. 14 , 16 , 17 , 43 45 Another recent study found that comorbid anxiety and depression may be increased in patients with PFP. 66 More detailed knowledge about the importance of such factors within PFP would not only improve our understanding of etiological mechanisms but might also inform development of psychologically targeted interventions.…”
mentioning
confidence: 99%